2016
DOI: 10.1155/2016/6539567
|View full text |Cite
|
Sign up to set email alerts
|

Weatherability of Polypropylene by Accelerated Weathering Tests and Outdoor Exposure Tests in Japan

Abstract: , carried out from 2010 to 2012, polyethylene reference sample (PE-RS) pieces and six types of polypropylene (PP) were subjected to accelerated weathering tests and outdoor exposure tests, resulting in the following findings. (1) The PE-RS was subjected to eight 100 h exposure tests in the same test machine. The accelerated weathering test machines of the participating institutes had high reproducibility. (2) The PE-RS CI values were greater when the temperature in the chamber was greater during accelerated we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…UVC did not damage the filtration layer even the exposure time was up to 90 minutes. Although UVC is proven to facilitate the degradation of polypropylene, short exposure targeted for disinfection of masks would not cause significant structural damage to the filtration layer [12].…”
Section: Structural Changesmentioning
confidence: 99%
“…UVC did not damage the filtration layer even the exposure time was up to 90 minutes. Although UVC is proven to facilitate the degradation of polypropylene, short exposure targeted for disinfection of masks would not cause significant structural damage to the filtration layer [12].…”
Section: Structural Changesmentioning
confidence: 99%
“…One example recently studied was the SLP of polymers used as high-voltage insulators on overhead electric power cables for trains in India [ 16 ]. More specifically to polyolefins, studies have been conducted that have shown the correlation between the durability of polypropylene in laboratory accelerated weathering compared to outdoor exposure in different regions of China [ 17 ] and Japan [ 18 ]. The correlation between the accelerated weathering of polyolefins in a laboratory and real-world outdoor exposure is critical to validate the performance of the polyolefin when used in a real-world application.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, standards governing the outdoor exposure methodologies for plastics, such as ASTM G113 [ 7 ], state that indoor accelerated tests should match results obtained through outdoor exposure. To this end, recent studies have been conducted that have shown the correlation between the durability of polypropylene in laboratory accelerated weathering compared to outdoor exposure in different regions of China [ 8 ] and Japan [ 9 ]. Furthermore, similar correlated studies have been conducted on polymers used as high-voltage insulators on overhead electric power cables for trains in India [ 10 ].…”
Section: Introductionmentioning
confidence: 99%